2022
DOI: 10.1055/s-0042-1757887
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Biotinidase Deficiency in the Pediatrics Population: Genotype–Phenotype Analysis

Abstract: Biotinidase (BTD) deficiency is a rare autosomal recessive metabolic disorder caused by insufficient biotin metabolism, where it cannot recycle the vitamin biotin. When this deficiency is not treated with supplements, it can lead to severe neurological conditions. Approximately 1 in 60,000 newborns are affected by BTD deficiency. The BTD deficiency causes late-onset biotin-responsive multiple carboxylase deficiency, which leads to acidosis or lactic acidosis, hypoglycemia, and abnormal catabolism. BTD deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 82 publications
(110 reference statements)
0
9
0
Order By: Relevance
“…In patients with profound BD, the neurological system is often the most affected, with over 70% of children exhibiting seizures, hypotonia, skin rash, or alopecia. Partial BD typically results in milder symptoms, which are often exacerbated by stress, such as prolonged fasting or infection [14,23,24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with profound BD, the neurological system is often the most affected, with over 70% of children exhibiting seizures, hypotonia, skin rash, or alopecia. Partial BD typically results in milder symptoms, which are often exacerbated by stress, such as prolonged fasting or infection [14,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…BD is genetic disorder, with the severity determined by the speci c mutations in the BTD gene. The complete absence of enzyme activity is usually due to deletions, insertions, or nonsense mutations, while missense mutations can have varied effects [14,24,25]. For instance, a study by Iqbal found the nonsense variant c.1275T > G in Austrian patients, leading to a premature stop codon and profound de ciency, although the affected infants did not exhibit symptoms initially [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis of BD can be life-saving and meets the major criteria for inclusion in newborn screening programs [ 29 ]. To this end, many countries worldwide, e.g., the USA, have included screening for BD in their national programs for newborn screening [ 35 ].…”
Section: Defects In Biotin Homeostasis/recycling: Treatment With Biotinmentioning
confidence: 99%
“…Enzyme activity assessment : Diagnosis of BD is mostly based on evaluating the enzyme activity in patient blood samples [ 30 ]. More specifically, biotinidase activity is determined following the hydrolysis of either natural or artificial substrates of the enzyme by means of various systems, including initially described radioassays [ 36 ], subsequent colorimetric or fluorometric assays [ 35 , 37 ], or more sophisticated assays, such as tandem mass spectrometry-based ones [ 38 ]. Patients with less than 10% mean normal serum enzyme activity are classified as having profound BD and those with 10–30% mean normal serum activity are classified as having partial BD [ 33 ].…”
Section: Defects In Biotin Homeostasis/recycling: Treatment With Biotinmentioning
confidence: 99%